Online extrinsic calibration between a 3D LiDAR and a monocular camera - Mharolkar, Sanat Rajesh (Nanyang Technological University, 2022)
For autonomous mobile robots, multiple sensors are being widely adopted as a way to enhance the perception ability of the robot. 3D LiDARs and cameras are the most commonly used sensors. A 3D LiDAR provides data in the form of unordered 3D coordinates of objects in the environment. A monocular camera provides data in the form of ordered color or intensity images. These two data complement each other and when fused together, they can provide a much better understanding of the scene. The first step to fuse the data from a 3D LiDAR and a camera is to obtain accurate calibration parameters between the two. Calibration is of two types – intrinsic and extrinsic. While the intrinsic calibration of each sensor is always done separately, this thesis is focused on the extrinsic calibration between the two sensors.